Local Wisdom in Blue Economy Development (Study of Ongko in Selayar Islands, South Sulawesi) - Muhammad Ihsan Maro (IECON: International Economics and Business Conference, 2024)
Ongko linguistically means savings or claims of ownership of something (resources). Local wisdom of Ongko is a knowledge of natural resource management based on kinship that has been used for generations by coastal communities in Selayar, South Sulawesi. This study aimed to find out more about the local wisdom of ongko, how the community used it and the opportunities to integrate it with the concept of blue economic development. This research was a qualitative study using data from literature studies, interviews, and observations. Meanwhile, the nature of this research was descriptive research that aimed to provide a detailed and clear picture of the problems studied. The results of the study showed that the local wisdom of ongko is still practiced by coastal communities in the Selayar and has the requirements to be able to meet the pillars of blue economic development. However, to maximize the fulfilment of the pillars of the blue economy, a series of steps need to be taken, including: providing reinforcement in order to upgrade Ongko into a joint management claim and strengthening the institutional management. Furthermore, it will lead to regulation of fishing times and use of fishing gear.